Transforming Islamic Higher Education Institutions Through Visionary Leadership - Fridiyanto, Fridiyanto; Firmansyah, Firmansyah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study explores how strategic leadership can drive institutional transformation towards excellence in Islamic higher education. A qualitative research approach with an ethnographic orientation was adopted, conducted at UIN Sulthan Thaha Saifuddin Jambi, Indonesia, over the course of one year, particularly during the university’s national accreditation preparation. Data were collected through three primary methods: participant observation in leadership meetings and quality assurance activities, in-depth interviews with 14 key informants (including university leaders, lecturers, and accreditation staff), and document analysis of institutional strategic plans and accreditation reports. Data analysis employed an inductive thematic procedure, in which interview transcripts, field notes, and institutional documents were analysed to identify emerging themes. The findings reveal that strategic leadership was realised through three key pillars: clear visionary direction, participatory management, and the integration of Islamic humanistic values into institutional governance. Despite facing challenges such as structural fragmentation, limited financial resources, and cultural resistance to change, leadership succeeded in mobilising collective commitment and aligning organisational efforts with accreditation goals. As a result, the university achieved the highest national accreditation rating (A). This study contributes theoretically by contextualising strategic leadership within faith-based educational settings in the Global South and highlighting the importance of moral authority, inclusive communication, and organisational synergy. Practically, the findings offer valuable insights for Islamic university leaders seeking to foster excellence under constrained conditions.